Synthesis Analgetic-Antiiflammation N-(4t-Buthylbenzoil)-p-Aminophenol by Using MgF2 Catalist - Siddiq, Hadi Barru Hakam Fajar; Eryani, Mikhania Christiningtyas; Suryaningsih, Farida (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Synthesis of N-(4t-buthylbenzoyl)-p-aminophenol has been done by reacting p-aminophenol and 4-tert- buthylbenzoyl chloride compounds with 1% MgF2 catalyst. N-(4t-buthylbenzoyl)-p- aminophenol as an antiinflamatory analgesic. Products were characterized by organoleptic test, melting point determination, TLC, UV/Vis Spectrophotometry, and infrared spectrophotometry. The results of the organoleptic test showed that N- (4t-butylbenzoyl) -p- aminophenol is powdered, gray and tasteless. Melting point of N-(4t- buthylbenzoyl)-p- aminophenol was 193 – 194 °C. TLC results showed that N-(4t-buthylbenzoyl)-p- aminophenol had two Rf values of 0.73 – 0.76 and 0.89 – 0.91. The results of UV wavelength scanning showed that N- (4t-butylbenzoyl) -p-aminophenol had two peaks at 290 and 294 wavelengths. Yield of N-4t- butylbenzoyl-p-aminophenol was 24.35%. Keywords: N-(4t-buthylbenzoyl)-p-aminophenol, MgF2, catalyst, an antiinflamatory analgesic